DAYA TARIK PEMBELAJARAN DI ERA 21 DENGAN BLENDED LEARNING - Riska Rahayu Roisiah; Akhlis Nastainul Firdaus; Hana Furaidah (Universitas Muhammadiyah Surabaya, 2023)
Education requires an innovative approach to ensure that learning is relevant and effective in the information and technology era. Blended learning, which combines face-to-face learning with digital technology, is becoming an increasingly popular learning approach. The aim of this article is to investigate and explain the benefits of blended learning in the modern era, exploring how this approach meets the needs and desires of today's students.